The genetic landscape of anaplastic pleomorphic xanthoastrocytoma. (6th November 2018) - Phillips, Joanna J.; Gong, Henry; Chen, Katharine; Joseph, Nancy M.; van Ziffle, Jessica; Bastian, Boris C.; Grenert, James P.; Kline, Cassie N.; Mueller, Sabine; Banerjee, Anuradha; Nicolaides, Theodore; Gupta, Nalin; et al.
Abstract: Pleomorphic xanthoastrocytoma (PXA) is an astrocytic neoplasm that is typically well circumscribed and can have a relatively favorable prognosis. Tumor progression to anaplastic PXA (WHO grade III), however, is associated with a more aggressive biologic behavior and worse prognosis. The factors that drive anaplastic progression are largely unknown. We performed comprehensive genomic profiling on a set of 23 PXAs from 19 patients, including 15 with anaplastic PXA. Four patients had tumor tissue from multiple recurrences, including two with anaplastic progression. We find that PXAs are genetically defined by the combination of CDKN2A biallelic inactivation and RAF alterations that were present in all 19 cases, most commonly as CDKN2A homozygous deletion and BRAF p.V600E mutation but also occasionally BRAF or RAF1 fusions or other rearrangements. The third most commonly altered gene in anaplastic PXA was TERT, with 47% (7/15) harboring TERT alterations, either gene amplification (n = 2) or promoter hotspot mutation (n = 5). In tumor pairs analyzed before and after anaplastic progression, two had increased copy number alterations and one had TERT promoter mutation at recurrence. Less commonly altered genes included TP53, BCOR, BCORL1, ARID1A, ATRX, PTEN, and BCL6 . All PXA in this cohort were IDH and histone H3 wildtype, and did not contain alterations in EGFR . Genetic profiling performed on six regions from the same tumor identified intratumoral genomic heterogeneity, likely reflecting clonal evolution during tumor progression. Overall, anaplastic PXA is characterized by the combination of CDKN2A biallelic inactivation and oncogenic RAF kinase signaling as well as a relatively small number of additional genetic alterations, with the most common being TERT amplification or promoter mutation. These data define a distinct molecular profile for PXA and suggest additional genetic alterations, including TERT, may be associated with anaplastic progression.